Head Loss Determination along Pipe of Drip Irrigation System using Small Pipe Emitter Made From Local Material - Mechram, Siti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Irrigation is an important factor in agricultural rop planting trickle or drip irrigation method is casier in operational, reguire a lower operational pressure and has a possibility to make from local material. Drip irrigation is a method of water application in form of drip on the soil surface or subsurface. Head loss along lateral is a common problem found in this method caused high variation in emitter discharge. This research aimed to determine emitter head loss along lateral, impact of emitter discharge on operational pressure, pipe diameter and treatment applied on lateral. This research utilized small pipe (1.6 mm in diameter) as emitter. Output discharge more collected and analyzed using complete random design method having 3 level of pressure (4, 6, and 8 psi) and 3 level of lateral diameter (1/3, Â¾, and 1 inchi). Head loss calculated using Darcy-Weisbach formula. Result showed a trend of increasing emitter discharge by increasing operational pressure. Increasing in emitter discharge was also found when a larger diameter used in system. Discreasing in head loss was detected when higher pressure a larger lateral used. Emitter uniformity coeffisien, calculated using cristiansen formula, was 91.2 % showing a selected emitter type was acceptable for drip irrigation method.Keywords: emitter, head lose, drip irrigation